2008
DOI: 10.1007/s11064-008-9615-y
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Hippocampal Cellular Distress may Explain the Behavioral Consequences of Repetitive Traumatic Experiences-A Proteomic Approach

Abstract: Early life traumatic experiences are associated with psychopathology in adulthood. This may be due in part to the effects of trauma on hippocampal development and protein expression. The purpose of the study was to investigate the effects of early life trauma and adult re-stress on ventral hippocampal protein expression. Adolescent rats (n = 19) were subjected to a triple stressor on post-natal day 28 followed 7 days later by the first re-stress session and 25 days later (post-natal day 60 = adulthood) by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
1
2
0
1
Order By: Relevance
“…Notably similar categories of proteins have been found to differ in their expression level following maternal separation [8], [9], chronic stress [50], [51], [52] and in the schizophrenic human brain [53], [54]. It should be noted that in our study, as in other similar ones using proteomic analysis based on 2-D gels [30], [55], there is a bias towards abundant, soluble proteins, with intermediate molecular weights.…”
Section: Discussionsupporting
confidence: 67%
“…Notably similar categories of proteins have been found to differ in their expression level following maternal separation [8], [9], chronic stress [50], [51], [52] and in the schizophrenic human brain [53], [54]. It should be noted that in our study, as in other similar ones using proteomic analysis based on 2-D gels [30], [55], there is a bias towards abundant, soluble proteins, with intermediate molecular weights.…”
Section: Discussionsupporting
confidence: 67%
“…However, an important unanswered question is the possible impact of chronic emotional stress during adulthood in animals that experienced stress during adolescence. In this regard, important neuroplasticity has been reported in the limbic systems of adult animals that were stressed during adolescence (Leussis et al, 2008;Toth et al, 2008;Uys et al, 2008Uys et al, , 2006Watt et al, 2009), which can affect the ability to cope with stress in adulthood. Indeed, studies have reported that stressful events in adulthood evoked greater behavioral changes in animals with a history of stress during adolescence (Avital and Richter-Levin, 2005;Tsoory et al, 2007).…”
Section: Perspective For Future Researchmentioning
confidence: 99%
“…Recently, some progress has been made using comparative proteomic studies to investigate ovarian cancer [2,[6][7][8][9][10][11][12][13]. Several studies have reported hippocampus proteome changes after chronic psychological stress [14][15][16]. However, little is known about the effects of chronic psychological stress on the proteome of ovarian cancer tissue.…”
mentioning
confidence: 99%